EDUKASI MANFAAT LITERASI MEMBACA DAN MENULIS DI SMK PGRI 3 BOGOR - Andriyani Siti Komalasari; Desmy Riani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2023)
Vocational High School (SMK) PGRI 3 BOGOR, North Bogor District. The problems that arise in this school are related to the students' lack of interest in reading and low interest in writing. To overcome these problems, an activity is needed to develop these skills. One of the programs that can develop reading and writing skills is the Educational Activities on the Benefits of Reading and Writing Literacy. Literacy activities do refer to a person's basic ability to optimize brain performance because it is often used for reading and writing activities. Reading helps a person to see the problem from his point of view and see it as a challenge that must be solved. There are many benefits of reading, including helping the development of thinking and clarifying ways of thinking, increasing knowledge, improving memory and understanding. By reading often, a person develops the ability to process knowledge, learn various disciplines, and apply it in life. Reading literacy culture is not an easy thing to build because it takes awareness and enthusiasm to bring about change. Reading literacy is not just an ordinary reading activity but an activity that can build culture itself.